2016
DOI: 10.1139/apnm-2015-0639
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of visual feedback on plantar- and dorsi-flexion maximal torque output

Abstract: The effect of visual feedback on enhancing isometric maximal voluntary contractions (MVC) was evaluated. Twelve adults performed plantar-flexion and dorsi-flexion MVCs in 3 conditions (no visual feedback, visual feedback, and visual feedback with target). There was no significant effect of visual conditions on dorsi-flexion MVC but there was an effect on plantar-flexion. Irrespective of whether a target was evident, visual feedback increased plantar-flexion MVC by ∼15%. This study highlights the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…The participants were instructed to develop MVCs as fast as possible. Visual feedback and encouragement [19,20] were given during all the MVC and RTD efforts. The RTD was calculated as the slope between two consecutive time units until the maximal achievable moment was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…The participants were instructed to develop MVCs as fast as possible. Visual feedback and encouragement [19,20] were given during all the MVC and RTD efforts. The RTD was calculated as the slope between two consecutive time units until the maximal achievable moment was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…In general, it improves test performance. For tests of isometric strength, performance increases 3% for the elbow flexors (317), 8% for the knee extensors (256), 8% for grip strength (40), and~16% for the ankle plantarflexors (410). For isokinetic tests of the knee extensors, visual feedback improves peak torque~6% (22,68,131,166,211).…”
Section: Administrative Strategies and The Test Environmentmentioning
confidence: 99%
“…The results of this study showed that the tongue strength was higher when the VF was applied than when VF was not applied. Previous studies have reported that VF is beneficial in increasing muscle contraction and muscle activation 5 , 6 ) . Park et al 7 ) reported that breathing exercise with VF improved pulmonary function and increased respiratory muscle activity.…”
Section: Discussionmentioning
confidence: 95%